3 - Les cultures africaines à l’épreuve de la colonisation* - Magloire Somé, (Afrika Zamani, 2022)
Through its negative thoughts about Africa and through the scale of value it ascribed to human societies, the nineteenth century civilising ideology resulted in the inferiorization of the black peoples and in a relegation to the sideline of history. This study aims at showing that if field work research in anthropology has made a contribution to improving how black Africa is perceived, the African elite’s struggle in the wake of World War II to push the perception struggle further oriented towards a nationalist and anti-colonialist agenda because they were convinced that only the recovery of the historical initiative would allow them to revalue and renew their cultures.